Rent Arrears And Their Implications In Public Housing - Salleh, Nor Aini; Johari, Noraini; Yusof, Nor’Aini (2008)
The need for housing occurs in tandem with the ongoing urbanisation process. Rapid urban growth has created a factor attracting the rural population toconverge in urban areas due to job opportunities available.